Graphics Recognition. New Trends and Challenges 9th International Workshop, GREC 2011, Seoul, Korea, September 15-16, 2011, Revised Selected Papers - Kwon, Young-Bin.; Ogier, Jean-Marc.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 9th International Workshop on Graphics Recognition (GREC 2011), held in Seoul, Korea, September 15-16, 2011. The 25 revised full papers presented were carefully selected from numerous submissions. Graphics recognition is a subfield of document image analysis that deals with graphical entities in engineering drawings, sketches, maps, architectural plans, musical scores, mathematical notation, tables, and diagrams. Accordingly the conference papers are organized in 5 technical sessions, covering the topics such as map and ancient documents, symbol and logo recognition, sketch and drawings, performance evaluation and challenge processing.
A Region-Based Method for Sketch Map Segmentation -- Ancient Documents Denoising and Decomposition Using Aujol and Chambolle Algorithm -- Efficient and Robust Graphics Recognition from Historical Maps -- On the Use of Geometric Matching for Both: Isolated Symbol Recognition and Symbol Spotting -- Notation-Invariant Patch-Based Wall Detector in Architectural Floor Plans -- A Recognition System for Online Handwritten Tibetan Characters -- Unified Representation of Online and Offline Hand Drawn Graphics Using Bezier Curve Approximation -- A Scoring Model for Clothes Matching Using Color Harmony and Texture Analysis.
Keywords: Computer science; Text processing (Computer science; Computer vision; Computer Science; Document Preparation and Text Processing; Image Processing and Computer Vision